Bone marrow transplantation in patients with storage diseases: a developing country experience - Lange Marcos C.; Teive Hélio A.G.; Troiano André R.; Bitencourt Marco; Funke Vaneuza A.M.; Setúbal Daniela C.; Zanis Neto José; Medeiros Carlos R.; Werneck Lineu C.; Pasquini Ricardo; Bonfim Carmen M.S. (Arquivos de Neuro-Psiquiatria)
Bone marrow transplantation (BMT) is a therapeutic option for patients with genetic storage diseases. Between 1979 and 2002, eight patients, four females and four males (1 to 13 years old) were submitted to this procedure in our center. Six patients had mucopolysaccharidosis (MPS I in 3; MPS III in one and MPS VI in 2), one had adrenoleukodystrophy (ALD) and one had Gaucher disease. Five patients had related and three unrelated BMT donor. Three patients developed graft versus host disease (two MPS I and one MPS VI) and died between 37 and 151 days after transplantation. Five patients survived 4 to 16 years after transplantation. Three patients improved (one MPS I; one MPS VI and the Gaucher disease patient), one patient had no disease progression (ALD) and in one patient this procedure did not change the natural course of the disease (MPS III).